The Existence of Jaranan Pogogan in Sugihwaras, Prambon, Nganjuk, Indonesia - Eko Gatut Febrianto; Djono Djono; Sudiyanto Sudiyanto (BIRCU, 2020)
Traditional art is a regional art as a part of national culture that must be preserved. Jaranan Pogogan is a traditional dance from Nganjuk. Jaranan Pogogan has been developing since 1950 but gradually became extinct in the 1980’s. The aim of the author is to raise the theme that Jaranan Pogogan can be preserved by the younger generation, with the theme of traditional arts expected to raise student interest in learning history. The research method used in this paper is qualitative and literature study data for data collection. The data obtained in this study passes the data analysis procedure that occurs simultaneously, namely data reduction, data presentation, and conclusion or data verification. The data generated in this study shows the relationship between the values of Jaranan Pogogan which is original of Nganjuk culture as a historical learning for the next generation that upholds the noble values, local wisdom and manners.